Assessment of Stakeholder Involvement and Borehole Water Projects Delivery in Kogi West Senatorial District, Nigeria - Adeyemi Adepoju; Tokunboh Obademi (Journal of Digital Food, Energy & Water Systems)
There is huge challenges in the supply of clean water for household consumption in many countries, in particular, Nigeria. Kogi West Senatorial District (KWSD) has witnessed more borehole projects in Nigeria but the challenge of clean water still persists. This has necessitated more research into the field of water resources to combat such challenges in line with the sustainable development goals (SDGs). This study assessed the effects of stakeholders’ involvement in KWSD, Nigeria, with a view to improving the delivery of borehole water projects in the study area. Data were collected through a structured questionnaire from 267 stakeholders comprising Lower Niger River Basin Development Authority (LNRBDA) staff, community leaders and community members that were selected using simple random sampling technique. The study objective was assessed with inferential statistics (Partial Least Square in Structural Equation Modelling). The results disclose the direct path coefficients for Initiation stage (bIS), Planning stage (bPS), Execution stage (“bES”), Monitoring and closure stage (bMS), Post construction stage (bPCS), Budget (cBG), Time Delivery (cTD) and Stakeholder’s Satisfaction (cSS). The results illustrated positives and significant relationship with bES -> cBG (β = 0.422, t = 5.708), bES -> cSS (β = 0.495, t = 6.366), bES -> cTD (β = 0.493, t = 7.422), bMS -> cBG (β = 0.164, t = 2.643), bPCS -> cTD (β = 0.257, t = 5.7084.440), and negative significant relationship with bMS -> cTD  (β = -0.184, t = 2.547) and  bPS -> cSS (β = - 0.182, t = 2.586). The study concludes that stakeholders’ involvement is a strong predictor of viable Borehole water projects delivery in the study area.